Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1089/rej.2015.1704
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: A Potential Anti-Oxidant Therapeutic Agent for Mitochondrial Dysfunctions and Related Disorders

Abstract: Mitochondria play a central role in cellular physiology. Besides their classic function of energy metabolism, mitochondria are involved in multiple cell functions, including energy distribution through the cell, energy/heat modulation, regulation of reactive oxygen species (ROS), calcium homeostasis, and control of apoptosis. Simultaneously, mitochondria are the main producer and target of ROS with the result that multiple mitochondrial diseases are related to ROS-induced mitochondrial injuries. Increased free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 241 publications
0
46
0
1
Order By: Relevance
“…The protective mechanisms of melatonin on mitochondria are multiple. These include, but are not limited to, a reduction of mitochondrial oxidative stress [150,151], preservation of the mitochondrial membrane potential [152,153,154], upregulation of the antiapoptotic mitochondrial protein/downregulation of the proapoptotic mitochondrial protein, Bax [137,155,156], increased efficiency of ATP production [59,157], reduced release of cytochrome C into the cytosol and the inhibition of caspase 3 activity [158,159]. …”
Section: Melatonin: a Potent Protector Of Mitochondriamentioning
confidence: 99%
“…The protective mechanisms of melatonin on mitochondria are multiple. These include, but are not limited to, a reduction of mitochondrial oxidative stress [150,151], preservation of the mitochondrial membrane potential [152,153,154], upregulation of the antiapoptotic mitochondrial protein/downregulation of the proapoptotic mitochondrial protein, Bax [137,155,156], increased efficiency of ATP production [59,157], reduced release of cytochrome C into the cytosol and the inhibition of caspase 3 activity [158,159]. …”
Section: Melatonin: a Potent Protector Of Mitochondriamentioning
confidence: 99%
“…It was confirmed that melatonin also plays an important role in improving the antioxidant defense in MS through upregulation of sirtuin 1 (SIRT1) and its target genes for MnSOD and CAT [100]. Moreover, melatonin is selectively taken up by mitochondrial membranes, which makes it a potential therapeutic tool in treating neurodegenerative disorders [50]. …”
Section: The Importance Of Antioxidants In Msmentioning
confidence: 99%
“…Subsequently, mitochondria become a site where it is responsible for the overproduction of ROS, therefore the main source of free radicals in cells. The elevation in hydrogen ion-electrochemical gradient is another result obtained from the transferring of metabolic substrates via ETC to molecular oxygen [40]. Evidences of Complex I and glutathione (GSH) deficiencies in substantia nigra are reported in most of the PD patients, hence supported the relationship between PD and mitochondrial dysfunction.…”
Section: Melatonin Rescues Mitochondrial Dysfunction In Pdmentioning
confidence: 98%